LEVOFLOXACIN-KETOPROFEN SALT FORMATION AND ITS EFFECT ON SOLUBILITY AND CHEMICAL STABILITY - Fauziah, Hana
Levofloxacin is an antibiotic that is unstable toward light. Ketoprofen is a non-steroidal antiinflammatory drug that is practically insoluble in water. This experiment produced levofloxacin ketoprofen salt (LK), which is expected to increase. The experiment was carried out by producing, characterizing, and testing the solubility and stability. LK is produced in a 1:1 molar ratio using solvent drop grinding. LK was characterized using electrothermal, PXRD, FTIR, and H-NMR instruments. Then, the solubility of LK was determined in distilled water pH 7.0, phosphate buffer pH 6.8 and pH 7.4 solvent, using a derivative UV spectrophotometry method, and its stability was tested by observing it for four weeks under test conditions and determining the concentrations using UV spectrophotometry. Differences in LK structures that indicate the formation of a new solid phase are shown by differences in melting points and diffraction patterns between LK and the physical mixture. Salt formation was demonstrated by the IR spectrum, which showed protonation of the piperazine group of levofloxacin and proton transfer from ketoprofen. This is confirmed by the H NMR spectrum, which shows protonation of the piperazine group of levofloxacin. Based on tests, the solubility of levofloxacin in LK decreased approximately 1.3 to 7.7 times in the solvents, while the solubility of ketoprofen in LK increased hundreds of times. LK was observed to be visually stable, and the reduction in levofloxacin levels in LK was 6.8 times lower than levofloxacin alone. Therefore, the formation of LK increased the stability of levofloxacin as well as the solubility of ketoprofen.